Activity‐Based Proteome Profiling Probes Based on Woodward's Reagent K with Distinct Target Selectivity. Issue 27 (9th May 2016) - Qian, Yong; Schürmann, Marc; Janning, Petra; Hedberg, Christian; Waldmann, Herbert
Abstract: Woodward's reagent K (WRK) is a reactive heterocyclic compound that has been employed in protein chemistry to covalently and unspecifically label proteins at nucleophilic amino acids, notably at histidine and cysteine. We have developed a panel of WRK‐derived activity‐based probes and show that surprisingly and unexpectedly, these probes are fairly selective for a few proteins in the human proteome. The WRK‐derived probes show unique reactivity towards the catalytic N‐terminal proline in the macrophage migration inhibitory factor (MIF) and can be used to label and, if equipped with a fluorophore, to image MIF activities in living cells. Abstract : Old dog—new tricks : Woodward's reagent K (WRK) is a reactive heterocyclic compound known to covalently and unspecifically label proteins. A range of WRK‐derived activity‐based probes were synthesized and shown to be fairly selective for a few proteins in the human proteome.